Different housing densities of laying hens in cages and their production, egg quality and feather score - Farinhas, Mateus Vianna Santos; Quintero, Juan Carlos Palomino; Moreira, Yuri Rodrigues; Rocha, Samuel de Sousa; Reis, Túlio Leite; Curvello, Fernando Augusto (Revista de Ciências Agroveterinárias, 2023)
The well-being of laying hens raised in cages is affected due to the smaller space available for them, which is in line with the growing pressure from a large number of consumers concerned about the conditions in which these birds are raised.The consequence of this lower housing density on productivity and the quality of life of the bird and the eggs produced by them must be evaluated. The aim of this study is to evaluate the production, egg quality, and welfare of laying hens reared in different housing densities in cages. At 28 weeks of age, 120 light Novogen White laying hens were distributed, after beak trimming, in 24 cages measuring 45 cm x 50 cm, in three different housing densities: 562.5 cm²/bird (four birds/cage), 450 cm²/bird (five birds/cage) and 375 cm²/bird (six birds/cage), with 8 repetitions each. The experimental diets were isoproteic and isoenergetic, based on corn and soybean meal. The trial period will comprise six cycles of 28 days each. The variables analyzed were: egg weight, yolk index, Haugh unit, yolk pigmentation, percentage of egg components and shell thickness (in millimeters). When the birds reached 44 weeks of age, the feather score was measured. Forty chickens per treatment were evaluated in four regions: chest, back, wings and hindquarters. This analysis consists of categorizing the birds according to three different scores, according to the size of the area without feathers in each region. It is expected that the reduction in the hen housing density in the cages will lead to higher production with better egg quality, also promoting better hen welfare.